A correlation of long term effects and radiation quality in the progeny of bystander cells after microbeam radiations: The experimental study of radiotherapy for cancer risk mitigation - N. Autsavapromporn (2018)
© Published under licence by IOP Publishing Ltd. The goal of this study is to investigate the role of radiation quality and gap junction intercellular communication (GJIC) in the propagation of delayed stressful effects in the progeny of bystander human skin fibroblasts cultures (NB1RGB). Briefly, confluent NB1RGB cells in the presence and absence of gap junction inhibitor (AGA) were exposed to ionizing radiation (IR) with a different linear energy transfer (LET) either 5.35 keV X rays (LET ∼6 keV/μm) or 18.3 MeV/u carbon (LET ∼103 keV/μm) microbeam radiations. Following 20 populations post-irradiation, the progeny of bystander NB1RGB cells were harvested and assayed for several of biological endpoints. Our results showed that expression of stressful effects in the progeny of bystander cells is dependent on LET. The progeny of bystander cells exposed to low-LET X rays showed the persistence of oxidative stress and it was correlated with the increased mutant fraction. Such effect were not observed after high-LET carbon ions. Interestingly, inhibition of GJIC mitigated the toxic effects in the progeny of bystander cells. Together, the results contribute to the understanding of the fundamental radiation biology relating to the high-LET carbon ions to mitigate cancer risk after radiotherapy. Furthermore, GJIC be considered as a critical mediator in the bystander mutagenic effect.